Upaya Satuan Sabhara Dalam Mencegah Pencurian Di Wilayah Hukum Polres Cirebon Kota - Muhammad Alzoeby Erbakan (Indonesian Journal of Police Studies, 2017)
The task of the Indonesian National Police is to take preventative measures rather than prosecution, therefore the operational units of the Indonesian National Police who are given the task of preventing and community service must be the main priority implemented by Sabhara members as Patrolmen. Patrol is a form of activity moving from one place to a certain place conducted by members of Sabhara Polri in order to prevent a crime, The high number of vehicle theft cases often occurs in the Cirebon City Region, so in this study only focuses on the Sabhara Patrol Unit in the Polres Area Cirebon City. This study uses a qualitative approach with a research location in the Legal Area of ​​Cirebon City Police, which was conducted in February 2020. The focus of this research is the Sabhara Unit's Efforts in preventing theft in the Cirebon City Police jurisdiction. The data sources are informants, processes and documents. Data collection techniques are Interview Guidelines, Document Inspection Guidelines, and Observation Guidelines. Data validity uses data triangulation. Data analysis uses the Interactive Analysis Model. General description of Harkamibmas in Cirebon City Police Station shows that the criminal case of motor vehicle theft is the highest crime case that occurred in the Cirebon City Police jurisdiction. Efforts made by the Cirebon Cirebon City Sabhara Unit are to carry out Patrols with stages, namely the preparatory stage, the implementation phase and the termination stage. The high case of motor vehicle theft is influenced by several factors, namely internal and external factors. Suggestions related to the Sabhara Unit's efforts to prevent cases of fraud, the Sabhara Unit should more often give warnings / appeals to people in the Cirebon City Police Legal area. The Sabhara Unit must innovate in efforts to prevent motor vehicle theft. The innovation is to carry out dialogical patrols. Meanwhile, to deal with the factors of criminal acts of theft of motorized vehicles, the Sabhara Unit must cooperate with each of the technical functions, related police and also elements of the Cirebon City Government.